A Review of Design and Policy Interventions to Promote Nurses' Restorative Breaks in Health Care Workplaces. (February 2016) - Nejati, Adeleh; Shepley, Mardelle; Rodiek, Susan
The nursing profession in the United States is on the precipice of a crisis. Nurses are essential to the health care industry, and maintaining quality nursing care is a primary concern of today's health care managers. Health care facilities report high rates of staff burnout and turnover, and interest in the nursing profession among younger students is declining. Health care leaders must improve nurses' job satisfaction, performance, and retention. However, they often overlook the need for nurses' respite and underestimate the value of well-designed staff break areas. An exhaustive and systematic literature search was conducted in the summer of 2014, and all studies found on the topic were reviewed for their relevance and quality of evidence. The existing literature about the main causes of nurses' fatigue, barriers that prevent nurses from taking restorative breaks, and consequences of nurses' fatigue for staff, patient, and facility outcomes demonstrates the pressing need for interventions that improve nurses' working conditions. Additional literature on the restorative effects of breaks and the value of well-designed break areas indicates that efforts to improve breakroom design can play an important role in improving nurses' job satisfaction and performance.